Construcción e instalación de un equipo modular para el estudio del caudal en función del nivel de líquido en vertederos triangulares - Díaz Fernández, Jolver Jossel (2022)
The main objective of the present work of thesis was: constructing and installing a modular equipment for the study of the flow in terms of the level of liquid in triangular drains. The present investigation is somewhat diligent, with quantitative focus, explanatory level of deepening and I design correlational. In the present investigation, firstly, a bibliographic revision on the fundamental equations of the flow of fluids was done. At a later time, one laid plans, he constructed and he installed each one of the components that conform the modular equipment. Finally, they came true in the modular team, four (4) you try for each one of the three (3) triangular drains. Results indicate that the minimal and maximum values of the level of liquid, that they obtained themselves when accomplishing the proofs of the modular team with the triangular drains of 30°, 45° and 60°, they are: (6 a 7.7) cm, (5.2 a 6.4 )cm y (4.6 a 6)cm, respectively. At a later time, the discharge coefficients for the triangular drains have been determined of 30°, 45° and 60°, these are: 0.5851, 0.5952 y 0.5961, respectively. Finally, the relations between the flow (fitting) with the level of liquid for the triangular drains have been determined of 30°, 45° and 60°, respectively, these are: ????=0.3704?5/2, ????=0.5824?5/2 and ????=0.813?5/2. Where it should be in m, in order to obtain ???? in m3/s. In this way he is trying on his general hypothesis and being responsible with the realistic general.